Effect of a Nutritional Behavioral Intervention on Intuitive Eating in Overweight Women With Chronic Kidney Disease - Pereira, Raíssa Antunes (2023)
Objectives: This study aimed to evaluate the impact of a nutritional behavioral intervention on intuitive eating (IE) scores of overweight non–dialysis-dependent women with chronic kidney disease and to investigate the relationship of IE scores with demographic, nutritional, and quality of life parameters in this group. Design and Methods: This is a prospective noncontrolled clinical trial of a behavioral multisession group intervention for dietary management. Each group comprised five to eight participants in 14 weekly or biweekly sessions lasting about 90 minutes each. The IE principles were discussed during the meetings. The IE scale 2, translated and adapted to the study population, with a four-factor model was applied to assess IE attitudes. The 36-Item Short-Form Health Survey questionnaire was applied to assess health-related quality of life. Results: Of the 33 patients who began participation in the study, 23 patients (median [interquartile range]: age = 62.0 years [58.0-68.0]; 52.2% with diabetes; body mass index = 32.6 kg/m2 [30.2-39.3]; estimated glomerular filtration rate = 28.0 mL/min/1.73 m2 [22.0–31.0]) completed the intervention. Except for the IE subscale Body-Food Choice Congruence, the IE total score and all its subscales (Unconditional Permission to Eat, Eating for Physical Rather than Emotional Reasons, Reliance on Hunger and Satiety Cues, and Body-Food Choice Congruence) improved after the intervention. In a cross-sectional analysis, more intuitive eaters were older and had better scores for health-related quality of life. Conclusions: The nutritional behavioral intervention embracing IE principles was effective to improve IE attitudes for this group of chronic kidney disease patients. These results are promising and may contribute to a paradigm change in the strategies to enhance motivation and adherence to dietary recommendations in this population.